IMPLIKATUR PADA WACANA ARGUMENTATIF DALAM SURAT PEMBACA HARIAN KOMPAS.COM EDISI AGUSTUS–SEPTEMBER 2021 (Kajian Analisis Wacana) - Sainil Amral; Briando Tumanggor (Universitas Batanghari, 2023)
The purpose of this study is to describe the use of Implicature in Argumentative Discourse in Kompas.com Daily Reader Letter. This research is descriptive qualitative research. The primary data in this research is in the form of quotations containing implicature contained in the reader's letter of Kompas.com daily. The result of this research can be concluded that there are 88 data quotations that contain implicature. Based on the 88 quotations, there are four forms of implied declarative sentences, interrogative sentences, imperative sentences, and explicative sentences. The distribution of the data presents 18 data are declarative sentence implicatures, 15 data are interrogative sentences, 7 data are imperative sentences, and 4 data are exclamative sentences. In terms of intent, there are three implicature intentions in the form of sentences meaning appeal, sentences meaning insinuation or prohibition, and sentences meaning warning. The distribution of the data presents as many as 13 data are sentences meaning appeal, 22 data mean insinuation or prohibition, and 9 data mean warning. Based on the results of the analysis, the implicature in the form of declarative sentences is the most found, and exclamative sentences are rarely found. In terms of intent, the meaning of sarcasm or prohibition is the most common, while the meaning of warning is the least common.